2005
DOI: 10.2166/wqrj.2005.048
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations in some Biotic and Abiotic Components of the Olezoa Wetland Complex (Yaoundé-Cameroon, West Africa)

Abstract: Concentrations of cadmium (Cd), copper (Cu), zinc (Zn) and lead (Pb) in water, sediments, fish organs and plants from two ponds of the Olezoa wetland complex were analyzed. Plants investigated were Cyperus papyrus, Enydra fluctuans, Ipomoea aquatica and Echinocloa pyramidalis. The fish species studied was the walking catfish Clarias lazera and the heavy metal concentrations were measured in the digestive tract, gills, flesh and liver. Average concentrations in water were 6 x 10 -2 ppm for Cd, 14.53 ppm for Cu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…Concerning the removal capacity of P. stratiotes for various nutrients from the WSR during all seasons tested, the values of nutrient removal observed after ten days of experimentation (TKN = 22–91%, N‐NH 4 + = 96–99%, P‐PO 4 3− = 95–99%, N‐NO 3 − = 17–98%) are similar or even higher to those that have been reported in other studies performed with this species .…”
Section: Discussionsupporting
confidence: 84%
“…Concerning the removal capacity of P. stratiotes for various nutrients from the WSR during all seasons tested, the values of nutrient removal observed after ten days of experimentation (TKN = 22–91%, N‐NH 4 + = 96–99%, P‐PO 4 3− = 95–99%, N‐NO 3 − = 17–98%) are similar or even higher to those that have been reported in other studies performed with this species .…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the concentrations of the heavy metals in the water were below those in the fish tissues which may be due to bio-accumulation. Similar findings by Fonkou et al (2005), Senarathne and Pathiratne (2007), Mohammed et al (2009) and Abdel-Baki et al (2011) also showed that the metal levels in fish were higher than the levels in both water and sediment, thus indicating bioaccumulation. However, there was no particular trend in the concentrations of heavy metals in all the fish organs with time.…”
Section: Discussionsupporting
confidence: 62%
“…In many cases, sewage from industries and agglomerations is piped or drained into the nearby aquatic ecosystems. As a result, surface and ground water are heavily polluted (Fonkou et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%